Effectiveness of Yoga-based Interventions on Chronic Low Back Pain (CLBP) – A Review of Randomized Controlled Trials - Bista, Sujana; Bista, Suman; Khadka, Rakshya; Poudel, Lisasha; Gaihre, Ganesh; Sapkota, Vijay (One Health Journal of Nepal, 2022)
Low back pain (LBP) is defined as the pain and stiffness above the inferior gluteal folds and below the costal margin. The LBP lasting for the duration of 12 weeks or more is considered chronic low back pain (CLBP). The age-standardized incidence rate of LBP observed in South Asia was 2,362.13 per 100,000 population. The global incidence of LBP increased by 50%, from 149,294,134.47 to 223,455,640.82 cases from 1990 to 2019 respectively. Studies reported that the yoga-based interventions reduces disability, pain, pain medicine, stress, anxiety, depression and negative emotions, and improves spinal flexibility, quality of life and positive emotions in patients with CLBP more effectively than usual care and physical exercise. Yoga appeared to be more effective than physical exercise in patients with CLBP which may be because of various aspects of yoga, such as maintaining the yoga postures, breath regulation, mindfulness, meditation, relaxation etc. which separated yoga from physical exercises. It is suggested that the government and public hospitals should take actions to employ the ancient science of yoga to cure the patients with CLBP to avoid side effects and complications.